Diagnostic value of the International Ovarian Tumor Analysis (IOTA) simple rules versus pattern recognition to differentiate between malignant and benign ovarian masses. Issue 3 (26th September 2019) - Dakhly, Dina M.R.; Gaafar, Hassan M.; Sediek, Mona M.; Ibrahim, Mohamed F.; Momtaz, Mohamed
Abstract: Objective: To compare the efficacy of the International Ovarian Tumor Analysis (IOTA) simple rules versus pattern recognition to differentiate between benign and malignant ovarian masses. Methods: A prospective cross‐sectional study conducted at Kasr El Aini Hospital, Cairo, between April 2016 and October 2018 of 396 women with ovarian masses measuring more than 5 cm who were candidates for surgery. All patients underwent two‐dimensional transvaginal sonography: level 2 with IOTA simple rules followed by level 3 with pattern recognition. Patients subsequently underwent ovarian cystectomy or oophorectomy and the specimens were examined histopathologically. Accuracy was measured by comparing sensitivity, specificity, positive predictive value, negative predictive value, and accuracy. Results: IOTA simple rules specified 44/50 cases as malignant and 220/242 as benign (sensitivity and specificity of 88.0% and 90.9%, respectively). Pattern recognition identified 83/94 cases as malignant and 281/302 as benign (sensitivity and specificity of 88.3% and 92.7%, respectively). No statistically significant difference in accuracy was found between the two methods. Conclusion: IOTA simple rules are an effective tool for detecting ovarian malignancy when performed by nonexpert sonographers. When results are inconclusive, pattern recognition should be performed additionally by an expert sonographer. Clinical trials registration: NCT02800031 Abstract : The IOTA simple rules are a useful tool for evaluation of ovarian masses when performed by nonexpert sonographers.